Ozone-induced Neurotoxicity: Mechanistic Insights and Implications for Neurodegenerative Diseases - Bjørklund, Geir; Gurgas, Leonard; Hangan, Tony (Current Medicinal Chemistry, 2026)
Ozone (O3), a reactive gas produced by sunlight-driven reactions involving nitrogen oxides and volatile organic compounds, presents serious risks to both respiratory and brain health. While its harmful effects on the lungs are well established, there is increasing evidence connecting ozone exposure to cognitive decline and neurodegenerative conditions like Alzheimer’s and Parkinson’s diseases. Ozone induces oxidative stress and systemic inflammation, and activates microglia, with the potential to reach the brain directly through the olfactory pathway. These mechanisms play a role in key neurodegenerative processes, such as the buildup of amyloid-beta, abnormal tau phosphorylation, and mitochondrial dysfunction. Drawing from findings in both animal and human studies, this review highlights the critical need to reduce ozone exposure to safeguard brain health and alleviate the growing impact of neurological disorders.
Keywords: oxidative stress